Physiological potential of seeds and morphological characterization of Campomanesia adamantium seedlings - Érica Fernandes Leão-Araújo; Eli Regina Barboza de Souza; Nei Peixoto; Francisco Guilhien Gomes-Júnior (Revista Brasileira de Fruticultura)
Abstract The cultivation of native fruit species depends on the existence of consistent technical and scientific information on the germination and vigor of seeds for efficient management by seedling producers. The evaluation of the physiological potential of seeds is performed through germination and vigor tests, which must be standardized to ensure the generation of accurate information. For Campomanesia adamantium, information on parameters for conducting physiological tests is scarce. The aims of this work were (i) to evaluate the effect of temperature and seed positioning on the substrate for seed germination and vigor, and (ii) to characterize and describe the essential structures and main types of seedling abnormality. After harvest, fruits were pulped and, after seed extraction, germination tests were carried out for 42 days at three temperatures (20, 25 and 30 °C), with seeds positioned in the germination substrate in two ways (between paper and on paper). Seed vigor was evaluated by means of the first germination count (performed on the 20th day) and the germination rate index. The temperature and substrate interaction did not influence variables under study. The position of seeds on the substrate did not influence the physiological potential results. No differences were observed between seed germination temperatures; however, seeds submitted to germination at 25 °C showed higher vigor compared to the other temperatures. Germination and vigor tests, based on seedling performance, should be performed at constant temperature of 25 °C and seed positioning between paper and on paper may be used. Germination in C. adamantium was characterized as epigeal.